ANALISIS FAKTOR YANG MEMPENGARUHI KONSUMSI BERAS DI PROVINSI ACEH - Meiza Aulia (Universitas Teuku Umar, 2022)
This research was conducted to know influence factors of rice consumption and how mauch the influence of these factors on rice consumption. This research was Ordinary Least Square (OLS) metodhology. Software was used by SPSS. The estimation result of the rice consumption showed that the changes in population with a coefficient of 0,082 have a t statistic value of 21,42 and the changes in the a mount of rice production with a coefficient of 0,041 have a t statistic value of 2,29, both variables significantly influence the changes in rice consumption because it have t statistics that is greater than t table (2,04).